A Rare Case of Gastric Perforation Secondary to Endoscopic Glue Injection for Gastric Varices - Khandagale, Varun; Sharma, Sandesh; Raghuwanshi, Pranav; Kumar, Sanjay (Journal of Digestive Endoscopy, 2021)
Gastric perforation is very rare. Gastric perforation following endoscopic glue injection for gastric varices (GVs) in patients with portal hypertension (PHT) has not been documented till date. They are associated with significant morbidity and mortality. We present a glue injection-induced gastric perforation in patients with PHT that has been treated with primary closure at our institution. To the best of our knowledge, this is the first case report of such complication following endoscopic glue injection for GVs. Such site of glue-induced perforation has not been reported in literature till date. A 38-year-old male patient having cirrhosis of liver with PHT underwent repeated upper gastrointestinal (GI) endoscopic procedures for recurrent upper GI bleed. After 20 days of third endoscopic procedure in which he had undergone glue injection for GVs, patient developed abdominal pain and abdominal radiograph was suggestive of bowel perforation. Emergency laparotomy was performed that showed gastric perforation near to glue injection site which was repaired with primary closure at our institution. Complication such as glue injection-induced gastric perforation has not yet been documented. It is potentially life-threatening. Early recognition may lead to a better prognosis through earlier intervention.
Keywords: perforation; gastric varices; glue injection